Challenges and new possibilities: african studies in Brazil and the South-South Connection - Livio Sansone (Mediações: Revista de Ciências Sociais, 2020)
African studies have had a profoundly political history in Brazil that shows that in this country, such as elsewhere, studying Africa is not a natural fact, but depends on political, geostrategic and economic interests as well as quite a degree of intellectual engineering. This article explores the originality of African studies in Brazil when compared with the Global North and addresses a set of challenges and bottlenecks that derive form the institutional fragility of such studies and the present adverse political climate in most of the Brics countries – Brazil, South Africa and India. In the last part the article expands on new paths that should be trailed for the development and consolidation of the South-South connection in African studies as seen from Brazil.